Effectiveness of donor notification and counseling of HIV-reactive donors in a tertiary care hospital from North India: An audit - Divya Bansal; Preeti Diwaker; Priyanka Gogoi; Malvika Singh; Anil Kumar Singh; Bharat Singh (Asian Journal of Transfusion Science)
INTRODUCTION: Blood banks are responsible for notification and counseling of the reactive donors besides screening for transfusion-transmitted infections (TTIs). Donor notification and counseling is essential to protect the health of the donor by early clinical intervention and to prevent secondary transmission of infection. AIM: The aim of this study was to determine the effectiveness of human immunodeficiency virus (HIV)-reactive donor notification and counseling in a tertiary care center. MATERIALS AND METHODS: An audit of the records of HIV-reactive donors over 2 years was conducted. The response rate of HIV-reactive donors on notification about reactive HIV status for one-to-one counseling was evaluated. Their attendance at an integrated counseling and testing center (ICTC) and compliance at an antiretroviral therapy (ART) clinic were also assessed. RESULTS: Out of 60,907 total donations, 124 (0.2%) donors were HIV reactive. One hundred and eleven were informed about their reactive status and the rest 13 could not be informed due to wrong demographic details in donor registration form. Eighty-seven (78%) reactive donors were informed by phone and the rest 24 (22%) were informed by confidential letter. Of the 111 informed donors, 62 (55.8%) came for one-to-one counseling (responders). Fifty-one (82.2%) responders visited ICTC after postdonation counseling. Over 6-month follow-up, 20/62 (32.2%) reactive donors were undergoing ART. CONCLUSION: The response rate of the donors to the notification and further receiving treatment is low in developing countries. Predonation screening and counseling by a trained counselor should be strengthened upon. Education of the donors about the TTIs can improve their knowledge and allay their anxiety.